PENGARUH PERILAKU BELAJAR PADA TINGKAT PEMAHAMAN AKUNTANSI DENGAN MINAT BELAJAR DAN KEPERCAYAAN DIRI SEBAGAI PEMEDIASI - Narindra, Ngurah Mayun; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to determine the mediation of interest in learning and self-confidence in the influence of learning behavior at the level of understanding of accounting students of Master of Accounting program (MAKSI), Faculty of Economics and Business (FEB), Udayana University. This study uses primary data by using questionnaires, which have fulfilled the validity and reliability test, distributed to 133 students of MAKSI FEB Unud program who qualify for sampling. The amount of data that 133 people can process. Data that has been tabulated then in the analysis using data analysis techniques, including classical assumption test, model feasibility test and path analysis techniques. Based on the calculation of path coefficient (p), it shows that interest in learning and confidence mediates the influence of learning behavior at the level of understanding of accounting.